1998
DOI: 10.1046/j.1365-3156.1998.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of antimicrobial use and antimicrobial resistance among healthy children in Bolivia

Abstract: SummaryOBJECTIVE To determine the incidence of antimicrobial-resistant, nonpathogenic Escherichia coli among healthy children aged 6-72 months in Camiri town and a rural village, Javillo, in south-eastern Bolivia. METHOD A community-based survey: stool samples were obtained from 296 healthy children selected by modified cluster sampling in Camiri and all 25 eligible children in Javillo. E. coli isolates were tested for antimicrobial susceptibility according to the standard disc diffusion method. By a questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 24 publications
(36 reference statements)
5
68
0
Order By: Relevance
“…The project monitors the dissemination of microbial drug resistance in the E. coli commensal microbiota of healthy children, which has largely been exploited as a useful indicator for similar studies (5,6,12,20,26). During the initial phase of the study, aimed at determining the rates of antimicrobial resistance in the populations of four different urban settings in the two countries, ceftriaxone-resistant isolates were detected in 4 of 3,208 (0.1%) children studied, and molecular characterization revealed the presence of CTX-M-type ␤-lactamase genes in the isolates from all four children.…”
Section: Discussionmentioning
confidence: 99%
“…The project monitors the dissemination of microbial drug resistance in the E. coli commensal microbiota of healthy children, which has largely been exploited as a useful indicator for similar studies (5,6,12,20,26). During the initial phase of the study, aimed at determining the rates of antimicrobial resistance in the populations of four different urban settings in the two countries, ceftriaxone-resistant isolates were detected in 4 of 3,208 (0.1%) children studied, and molecular characterization revealed the presence of CTX-M-type ␤-lactamase genes in the isolates from all four children.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size of 400 children was selected to achieve 80% power with a type 1 error of 5% of detecting any particular exposure with a risk ratio of two for carriage of a resistant organism, assuming 100% carriage of enteric E. coli in the sampled children and a resistance level of at least 20% in the population. Studies in South America have found high carriage rates of resistant E. coli , 32,33 suggesting that this was an adequate sample size to achieve the study's objectives. To assure an adequate range of values of risk factors, in particular of community-level variables such as resistant E. coli carriage levels and antibiotic sales, the study was conducted in 16 zones throughout the country, with at least 25 households in each zone.…”
Section: Study Sitementioning
confidence: 99%
“…This study aimed to assess the influence of various medical, agricultural, and environmental exposures at the individual, household, and community levels in determining the risk of young children in a developing country for carrying antibiotic-resistant E. coli . Escherichia coli was selected for study because they are common in humans and animals, can cause disease, have been used to gauge the spread of acquired resistance, 32,33 and might serve as markers of the transfer of resistance from animal to human intestinal microflora. Peru was chosen as the study site because of its high but variable levels of medical and agricultural antibiotics usage and generally weak but somewhat mixed sanitation and protection of water, thereby enabling simultaneous examination of several risk factors for carrying resistant organisms.…”
Section: Introductionmentioning
confidence: 99%
“…A substantial proportion of healthy people in develop ing countries are colonised with multidrug-resistant bacteria. [6][7][8][9][10][11] Common bacterial pathogens such as Escherichia coli, Salmonella spp, or Streptococcus pneumoniae are often multidrug resistant in these settings. Mycobacterium tuberculosis, including multidrug-resistant M tuberculosis, is also common in low-income to middleincome countries, and extremely drug resistant strains have emerged.…”
Section: Introductionmentioning
confidence: 99%